Framing Contracts: Why Loss Framing Increases Effort - Richard R. W. Brooks; Alexander Stremitzer; Stephan Tontrup (SSRN, 2012)
Recent evidence from the field (Hossain and List, 2009) suggests that contracts framed in terms of a loss (a deduction is taken for failing to meet a threshold) lead to greater effort than contracts framed in terms of a gain (a bonus is given for meeting a threshold). We investigate two explanations for this framing effect in a laboratory setting. First, we find that the loss frame communicates the expectation that achieving the bonus is the default and that our subjects comply with this expectation. Second, we find evidence for an endowment effect, even though the bonus is just a monetary payment that subjects do not even have in their possession.
Keywords: K12; C91; L14; J41; 340; Contract design